Estudo da troca iônica multicomponente pela zeólita NaY em colunas de leito fixo - Ostroski, Indianara Conceição (2009)
This thesis aimed to study the uptake mechanism of Fe²+ , Zn²+ and Na+ in zeolite Y as exchanger in fixed bed columns considering dynamic conditions. Monocomponent, bicomponent and predictive systems were investigated. In this context, different mathematical models were evaluated to describe the equilibrium: the mass action law, the multicomponent adsorption isotherms and the classical thermodynamics models (IAST - Ideal Adsorbed Solution Theory, RAST - Real Adsorbed Solution Theory and VSM - Vacancy Solution Model). The dynamic runs were carried out in fixed bed columns operated up flow at 30oC, ith diameter particle of 0.18 mm and flow rate of 8 mL/min. For Fe-Na, Zn-Na and Fe-Zn binary systems, the breakthrough curves were obtained at total feed concentrations of 1, 2 and 3 meq/L. The breakthrough curves for the ternary system Fe-Zn-Na obtained in total feed concentration of 3 meq/L. It was seen that the ideal mass action law, the non-ideal mass action law the adsorption models fit successfully the equilibrium data. However, the non-ideal mass action law, which requires the calculation the activity coefficient in the liquid and solid phases, was the model that best adjusted the data of binary equilibrium. Considering the equilibrium constant obtained by such model, the following sequence of selectivity of zeolite Y was observed: Zn²+ > Fe²+ > Na+. The non-ideal mass action law and the inhibition Langmuir isotherm model represented the ion exchange equilibrium of ternary system. The non-ideal mass action law was able to reasonably predict the behavior of the equilibrium in ternary system based on parameters obtained for the binary system. On the other hand, the inhibition Langmuir isotherm model has not been able to satisfactorily predict the equilibrium data of ternary system. It is a consequence of the poor adjustment of such model to the single equilibrium data for Zn²+ and Na+.